Impact heating and the hidden Hadean - Tim E. Johnson; Craig O’Neill; Simon Turner; Christopher L. Kirkland (Science, 2026)
The nature of Earth’s crust during the Hadean eon [≥4.03 billion years ago (Ga)] is uncertain. Numerical models of early Earth geodynamics emphasize the control of mantle temperature but generally consider only internally derived heat, despite empirical evidence for an intense Hadean impact flux. Using a stochastic model of that flux, we show that the time-integrated heat due to impacts would have dwarfed that produced internally throughout the Hadean. Earth’s Hadean crust would have been extensively molten at depths below a few kilometers, causing gravitational segregation of dense, iron- and magnesium-rich material and driving average crustal compositions to become increasingly silica rich. Globally, impact heating would have become much less important after 3.9 Ga, allowing the crust to thicken. That enduring continental crust appeared around this time is likely not a coincidence.